PENERAPAN PENDEKATAN KONSTRUKTIVISTIK UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF PADA SISWA PAUD BETHE JEROL KECAMATAN ARU SELATAN KABUPATEN KEPULAUAN ARU - Junita L. Kundre; R Tutupary; Maria Pokar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research addresses low cognitive abilities among early childhood students at PAUD Bethel Jerol in South Aru District due to teacher-centered learning approaches and suboptimal teaching methods. The study aims to determine whether constructivist learning approach can enhance cognitive abilities and learning activities of 11 students (5 boys, 6 girls). Using classroom action research methodology conducted over two cycles from June 3-11, 2024, each cycle consisted of planning, implementation, observation, and reflection stages. Data collection employed observation sheets, documentation, and cognitive ability tests. Results demonstrate significant improvements: student positive activities increased from 26% in cycle I to 42% in cycle II, while average cognitive scores rose from 6.3 to 7.2. The number of students achieving minimum completeness criteria (score ≥7.8) increased from 1 student (3%) to 12 students (34%). The research concludes that constructivist approach effectively improves both student activities and cognitive learning outcomes by allowing children to build knowledge based on their experiences through direct observation and active participation.